Fate of polycyclic aromatic hydrocarbons in the phytoremediation of different hydrocarbon contaminated soils with cotton, ryegrass, tall fescue, and wheat - Zeng, Yunmin; Wang, Shijie; Huang, Fan; Luo, Qiang; Ren, Bing; Abo El-Maati, Mohamed F.; El-Sappah, Ahmed H. (Frontiers in Plant Science, 2025)
IntroductionPhytoremediation is a promising strategy for cleaning up polycyclic aromatic hydrocarbon (PAH)-contaminated soils. This study investigated the effectiveness of four plant species—cotton, ryegrass, tall fescue, and wheat—in enhancing PAH removal from soils contaminated with diesel oil, PAHs, and aged oily sludge.MethodsAged oily sludge-contaminated soil was artificially prepared, and the selected plants were cultivated in different hydrocarbon-contaminated soils (diesel oil, PAHs, and oily sludge). The fate of PAHs was analyzed by measuring their distribution in rhizospheric soil and plant tissues. Root concentration factors (RCFs) and transpiration stream concentration factors (TSCFs) were used to evaluate PAH translocation and accumulation in plant tissues and their interactions with the rhizosphere.ResultsThe study demonstrated that plants enhanced PAH removal by 20%–80%, with wheat showing the highest efficiency. PAH removal was generally more effective in oily sludge-contaminated soil than in diesel oil or PAH-contaminated soil. Plant uptake of PAHs accounted for 2%–10% of total removal and exhibited a strong linear correlation with root weight. RCFs were linearly correlated with LogKow (3–6), indicating that the four plant species did not significantly concentrate PAHs in their roots.DiscussionThe findings confirm the potential of phytoremediation for PAH-contaminated soils, particularly using wheat as an effective species. The low RCFs and TSCFs suggest that PAH uptake was limited, implying that rhizodegradation and microbial interactions may play a more critical role than direct plant accumulation. This study supports phytoremediation as a cost-effective and eco-friendly alternative to conventional soil remediation methods, reducing economic and environmental burdens.